Natural history of naevi: a two‐wave study. (1st February 2021) - Ribero, S.; Zugna, D.; Spector, T.; Bataille, V.
Summary: Background: Naevi number changes with age. Thus, a better understanding of naevus biology will shed more light on the genetic and environmental factors involved in melanoma development. Objectives: To use a two‐wave study to better understand the evolution of naevi in healthy adults. Methods: This study is a prospective two‐wave study based on adult twins from the TwinsUK registry ( n = 414) who underwent total body naevus counts with an interval of at least 15 years. A negative binomial hierarchical model with two levels, the individual and the twin pair, was used to estimate expected changes in naevus count between the first and second visit, at any specific body site and on the whole body. The model was adjusted for age, calendar year at the first visit, height and skin type. Results: The mean age of participants was 46 years at the first visit and 63 years at the second visit (the mean elapsed time between visits was 17 years). An increase in naevus count was observed in 235 (57%) participants and a decrease was observed in 166 (40%). The mean difference in total naevus count between the two visits was nine. The expected total body naevus count increased, on a logarithmic scale, by 0·28 [95% confidence interval (CI) 0·16–0·40] with a change in the incidence rate of total body naevus count of 32% (95% CI 17–49%). However, the observed increase in naevus count over time was observed only on the upper parts of the body, whereas there was no evidence of an increase on the lower parts. Conclusions: Naevus counts increased slightly over time at older ages, but this was dependent on body site. The overall decrease in naevus counts previously reported in cross‐sectional studies has not been confirmed by this longitudinal study.